ISSUES OF FINANCIAL SECTOR DEVELOPMENT IN THE CENTRAL ASIAN COUNTRIES - Muyassar Mirzakarimova; Lola Azimova (Journals Park Publishing, 2023)
This article is devoted to the consideration of the issues related to the development of the financial sector in Central Asian countries as a factor of sustainable development. In addition, the article analyzes the areas of banking system reforms in the countries of the region, the process of structural changes in the economy made through investments, problems with the improvement of the investment environment.
Keywords: financial sector, banking system, lending organizations, investment, national funds, structural changes, sustainable development.